Machining: State-of-the-Art 2022 - Silva, Francisco J. G.; Fernandes, Filipe Daniel; Sousa, Vitor Fernando Crespim (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Machining continues to be a hot topic within the field of Mechanical Engineering, due to the fact that it allows for high precision and surface quality. Studies around machining remain extremely active, and there is still a strong demand for knowledge and development in this area. Sectors, such as the aeronautical industry, aerospace industry, defense industry, automotive industry and mold industry, are just some of the sectors that depend heavily on this manufacturing process to produce the components that the market requires. The industry continues to require increasingly reliable and competitive solutions, and it is up to science to study means of achieving these ends. This reprint seeks to compile a series of articles that contribute to the increasing knowledge in this area.